The Efforts to Improve the Creativity of Early Children through Project Learning in PAUD Durian 1 Ciputat Timur (Indonesian Journal of Early Childhood Education Studies, 2022)
This study aims to determine the improvement of early childhood creativity through project learning. The methodology in this study uses qualitative with classroom action research methods through observation and interviews. The research subjects consisted of 15 students, the data analysis technique used triangulation of data sources with the stages of data processing according to Miles and Huberman. The results of data analysis indicate that the development of children's creativity can be improved by using project learning methods through playing blocks and finger painting. Judging from the enthusiasm and enthusiasm of students in doing activities playing blocks and finger painting. Children's creativity has begun to be seen where children are able to make a work of blocks, children no longer hesitate to color and add other shapes to the picture. Apart from that, some children can play activities by not imitating the work of their own friends and can follow instructions from the teacher. Keywords: Creativity, Early childhood, Project learning